Distribution and habitat use patterns of southern right whales, Eubalaena australis, off Uruguay - Costa , Paula; Piedra, Mariana; Franco, Paula; Paez, Enrique (J. Cetacean Res. Manage., 2023)
Aerial surveys and behavioural observations from land were conducted 2001-03, between July and November, to evaluate the status and habitat use patterns of the southern right whale (Eubalaena australis) along 220km of the Uruguayan Atlantic coast. Photo-identification was carried out only during the aerial surveys, and group composition as well as spatial and temporal distribution was studied. For the analysis of distribution, the area was divided into four zones. Behaviour was studied from nine fixed points along the coast, analysing the relative frequency of three states (interacting, travelling and resting) and five events (flipper, spy hopping, tail-up, belly-up and flipper slap). Most individuals (90%) were seen from August to October (H=16.446, p=0.003) and there was no significant difference in sightings between the four zones (H=5.11, p=0.163). In 80 sightings, 174 individuals were observed, of which 8% (n=14) were cow-calf pairs and 92% (n=160) were unaccompanied whales (whales without calf). Out of these, 76.9% (n=123) were found in groups that ranged 2-13 individuals (mean=3.4; SD=2.7) and the rest (23.1%; n=37) were solitary. Sixty individuals were identified, one of which was re-identified within a season. Focal sampling on unaccompanied whales took place on ninety-three occasions; 64 on groups and 29 on solitary individuals. For groups, the most frequent behavioural state was interaction (57.8%), and all events were observed, spy hopping being the most frequent. Given the high proportion of unaccompanied whales and interacting groups recorded, Uruguay is thought to be an important social area for the species, where behaviour similar to those previously described as courtship and mating were observed. The dynamics of the different categories of individuals off the Uruguayan coast is discussed and investigation priorities are suggested.